Critical Awareness Preliminary: Leadership of Girls Post Ethnic Conflict in West Kalimantan - Fernando, Joshua; Sarwoprasodjo, Sarwititi; Muljono, Pudji; Marta, Rustono Farady (Jurnal Komunikasi, 2022)
door for every child, especially girls, to have equal opportunities to participate widely regardless of their gender status. The West Kalimantan Children's Forum exists as a means for girls to express their opinions and contribute more to the full fulfilment of children's rights. The historical background of past ethnic conflicts makes the reconciliation of ethnic conflicts in West Kalimantan continue to this day. Indirectly the participation of children, especially girls, is very calculated for establishing harmony between ethnicities and all groups of people in West Kalimantan. The study is aimed to the initial review of phenomenological studies in looking at the critical awareness process through participatory intercultural communication processes carried out by female leaders who are children of Dayak and Madurese ethnicity at the West Kalimantan Children's Forum. This research uses a qualitative method drawn from a phenomenological perspective so that the process of individual experience becomes very important as a witness to the journey of reconciliation. The theory of Liberation Education from the perspective of Paulo Freire is used to see how far the process of critical awareness through participatory intercultural communication processes can encourage individuals to proceed in reconciliation for the sake of inter-ethnic harmony through participation as a member of the West Kalimantan Children's Forum. The subject of this research involved girls as members of the Children's Forum in the form of in-depth interviews to see to what extent the public sphere provides an opportunity to process together reconciliation which is still ongoing today. This study explains that the achievement of critical awareness in girls' participation in conflict reconciliation still has to go through several stages of awareness, such as magical and naive. The process of openness, learning, and accepting differences, will make girls' leadership reach the highest critical awareness and be able to participate fully in development that involves quality young people.